Sensory Abilities of Horses and Their Importance for Equitation Science - Rørvang, Maria Vilain; Nielsen, Birte L.; McLean, Andrew Neil (Frontiers in Veterinary Science, 2020)
Vision, hearing, olfaction, taste, and touch comprise the sensory modalities of most vertebrates. With these senses, the animal receives information about its environment. How this information is organized, interpreted, and experienced is known as perception. The study of the sensory abilities of animals and their implications for behavior is central not only to ethology but also to animal welfare. Sensory ability, perception, and behavior are closely linked. Horses and humans share the five most common sensory modalities, however, their ranges and capacities differ, so that horses are unlikely to perceive their surroundings in a similar manner to humans. Understanding equine perceptual abilities and their differences is important when horses and human interact, as these abilities are pivotal for the response of the horse to any changes in its surroundings. This review aims to provide an overview of the current knowledge on the sensory abilities of horses. The information is discussed within an evolutionary context and also includes a practical perspective, outlining potential ways to mitigate risks of injuries and enhance positive horse-human interactions. The equine sensory apparatus includes panoramic visual capacities with acuities similar to those of red-green color-blind humans as well as aural abilities that, in some respects exceed human hearing and a highly developed sense of smell, all of which influence how horses react in various situations. Equine sensitivity to touch has been studied surprisingly sparingly despite tactile stimulation being the major interface of horse training. We discuss the potential use of sensory enrichment/positive sensory stimulation to improve the welfare of horses in various situations e.g. using odors, touch or sound to enrich the environment or to appease horses. In addition, equine perception is affected by factors such as breed, individuality, age, and in some cases even color, emphasizing that different horses may need different types of management. Understanding the sensory abilities of horses is central to the emerging discipline of equitation science, which comprises the gamut of horse-human interactions. Therefore, sensory abilities continue to warrant scientific focus, with more research to enable us to understand different horses and their various needs.